Patch-Clamping Fly Brain Neurons - Fernandez Chiappe, Florencia (2022)
The membrane potential of excitable cells, such as neurons and muscle cells, experiences a rich repertoire of dynamic changes mediated by an array of ligand- and voltage-gated ion channels. Central neurons, in particular, are fantastic computators of information, sensing, and integrating multiple subthreshold currents mediated by synaptic inputs and translating them into action potential patterns. Electrophysiology comprises a group of techniques that allow the direct measurement of electrical signals. There are many different electrophysiological approaches, but, because Drosophila neurons are small, the whole-cell patch-clamp technique is the only applicable method for recording electrical signals from individual central neurons. Here, we provide background on patch-clamp electrophysiology in Drosophila and introduce protocols for dissecting larval and adult brains, as well as for achieving whole-cell patch-clamp recordings of identified neuronal types. Patch clamping is a labor-intensive technique that requires a great deal of practice to become an expert; therefore, a steep learning curve should be anticipated. However, the instant gratification of neuronal spiking is an experience that we wish to share and disseminate, as many more Drosophila patch clampers are needed to study the electrical features of so many fly neuronal types unknown to date.